Essential characteristics of sleep from the occupational science perspective/ Características essenciais do sono na perspectiva da ciência ocupacional - Leive, Lorena; Morrison, Rodolfo (Cadernos Brasileiros de Terapia Ocupacional, 2020)
Sleep occupation bears interesting and particular characteristics when described from the occupational science perspective. This theoretical essay examines literature from different disciplines, as well as key concepts of Occupational Science to contribute to this perspective of sleep. Firstly, the article describes sleep occupation as a pillar of health, wellbeing, and quality of life in human beings. Then, the essay focuses on how the occupation emerges in early life in the context of family routines and rituals. Daily participation and sleep are analyzed in response to two major questions that have arisen related to this occupation: how participation can be observed in an occupation characterized with periods of a reversible loss of consciousness, and how these periods could be integrated into a unique and particular occupation such as sleep. Afterward, the essay focuses on orchestration and synchronization as essential processes in the occupation. Sleep occupation meanings are described as a great contribution to people’s identity and sense of belonging. Finally, sleep occupation is proposed as an occupational right. Understanding crucial sleep characteristics offer a broad vision from an occupational perspective. The possibility to examine this essential occupation for human life opens an opportunity to enrich the vision about what individuals do to sleep, how they organize it, and promote or not their health, besides how contextual elements support or not this occupation.